Predictive Approaches to Obsolescence in Automotive Electronics Based on Life Cycle Concepts - Karthika P; Dr. P. Prabhusundhar (Utilitas Mathematica, 2025)
An automotive electronics component typically progresses through seven distinct life cycle stages: Introduction, Growth, Maturity, Decline, Phase-out, Discontinuance and Obsolescence, and Special Cases. The obsolescence of Automobile electronic components significantly impacts the life cycle costs of long field-life systems such as automotive. These life cycle curves serve as critical tools for analyzing part longevity and forecasting availability trends. This paper presents a forecasting methodology that predicts both the time to obsolescence and the different stages of a part's life cycle. The approach incorporates both market dynamics and technological trends through a continuous analysis of sales data. The resulting models provide engineers with the ability to strategically plan for the deployment and maintenance of long life products, using forecasts of the life spans of their component parts. The methodology is specifically applied to integrated circuits, with obsolescence forecasts demonstrated for Advanced Driver Assistance Systems. The overarching objective is to minimize design revisions, reduce inventory and sustainment costs and lower the total life cycle expenses of the product. Manufacturers with strong market share and profitability tend to remain stable, lowering obsolescence risk. Overall, the current device/technology group remains supportable longer but requires ongoing risk monitoring due to sourcing constraints and evolving application demands.